Focus on Nivolumab in NSCLC - Cortinovis, Diego L.; Canova, Stefania; Abbate, Marida; Colonese, Francesca; Bidoli, Paolo (Frontiers in Medicine, 2016)
Immunotherapy is changing the treatment of non-small cell lung cancer (NSCLC). The PD-1 inhibitor nivolumab has demonstrated meaningful results in terms of efficacy with a good safety profile. The novel approach of treating NSCLC using immunotherapy has still unsolved questions and challenging issues in regard to the optimal selection of the patient, its role in first line of treatment, the individualization of the correct methodology of radiologic assessment and efficacy analysis, the best management of immunomediated adverse events, and how to overcome the immunoresistance.